FACTOR ANALYSIS OF ACTIVE LEARNING MANAGEMENT OF SECONDARY SCHOOL TEACHERS UNDER THE OFFICE OF THE BASIC EDUCATION COMMISSION - Worathadasawat, Wishirata; Chaowachai, Sathiraporn; Kornpuang, Anucha (Journal of Education and Innovation, 2024)
This research aimed to explore the factors of Active learning management of secondary teachers under the office of the basic education commission by using the exploratory research methodology. The sample of this research was 344 secondary school teachers in the lower northern part of Thailand that were sampled by stratified random sampling from school size. The data were collected by using a 5-level rating scale questionnaire with a reliability of 0.92 of 37 items. Exploratory factor analysis was used to analyze the data. Then extracted components by Principal component analysis and orthogonally rotated components axis with Varimax rotation method. The result showed that the composition of Active learning management of secondary teachers consists of five components: 1) Multi skill Learning Design, 2) Preparation Process for Learning Activities, 3) Self-Learning Facilitating, 4) Media and Technology Using for Self-Learning, and 5) Evaluate to Reinforce learner. All of these components were able to explain the variance of Active learning management of secondary teachers at 84.05 percent.